2000
DOI: 10.1016/s0735-1097(00)00865-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic no-reflow phenomenon as a predictor of adverse long-term outcome in patients treated with percutaneous transluminal coronary angioplasty for first acute myocardial infarction

Abstract: Angiographic no-reflow phenomenon strongly predicts long-term cardiac complications after AMI; these complications are possibly associated with LV remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
317
3
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 509 publications
(362 citation statements)
references
References 35 publications
20
317
3
10
Order By: Relevance
“…LV function and remodeling after AMI are considered to be influenced by many factors including no-reflow phenomenon, 10) time for myocardial ischemia, infarct size, wall stress, and medications such as angiotensin converting enzyme inhibitors (ACE-I), β-blockers, nicorandil, 32,33) and human natriuretic peptide. 34,35) Several recent trials have suggested that nicorandil preserves LV function by reducing the no-reflow phenomenon, 32,33) and our anterior AMI patients were routinely treated with nicorandil if their blood pressures allowed it.…”
Section: Discussionmentioning
confidence: 99%
“…LV function and remodeling after AMI are considered to be influenced by many factors including no-reflow phenomenon, 10) time for myocardial ischemia, infarct size, wall stress, and medications such as angiotensin converting enzyme inhibitors (ACE-I), β-blockers, nicorandil, 32,33) and human natriuretic peptide. 34,35) Several recent trials have suggested that nicorandil preserves LV function by reducing the no-reflow phenomenon, 32,33) and our anterior AMI patients were routinely treated with nicorandil if their blood pressures allowed it.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,20,21 Most of them studied very small AMI populations treated with different reperfusion strategies at different times and were focused mainly on inhospital or intermediate prognosis. Our prospective study provides information on the prognostic role of microvascular dysfunction by MCE in a quite homogeneous and unselected study population with AMI successfully treated by means of primary PTCA.…”
Section: Microvascular Dysfunction and Long-term Clinical Outcomementioning
confidence: 99%
“…CME causing transient “no blood flow” or “slow flow” is the independent predictor of long-term poor prognosis in patients with acute myocardial infarction. [2] Furthermore, CME can also lead to progressive myocardial malfunction, including overt myocardial infarction, contractile dysfunction, arrhythmias and coronary reserve reduction. [4,5] Once CME occurs, clinical outcomes of such patients are not improved by using coronary thrombolysis agents, nitroglycerin and platelet GPIIb/IIIa receptor antagonists or direct thrombectomy.…”
Section: Introductionmentioning
confidence: 99%